Rethinking malaria elimination: a perspective on challenges and solutions in Angola - Edmilson Serra Domingos (Malaria Journal)
Abstract Background Multiple challenges hinder malaria control in Angola, including climatic variability, ineffective vector control, population displacement, socioeconomic inequalities, and increasing resistance to anti-malarial drugs and insecticides. These barriers have been further exacerbated by the COVID-19 pandemic, disrupting healthcare services and reversing prior gains. Despite a 36% reduction in malaria mortality since 2000, Angola remains off track to meet the Global Technical Strategy (GTS) targets for 2025, with no significant progress recorded in reducing malaria mortality between 2015 and 2023. Perspectives This paper analyses Angola’s malaria landscape, emphasizing that persistent healthcare system weaknesses such as financial instability, workforce shortages, poor disease surveillance, and regional disparities in intervention coverage, necessitate urgent, tailored responses. Drawing from lessons learned in successful malaria elimination programmes in Cabo Verde, Algeria, China, and the recent WHO recommendations, the study recommends the implementation of three integrated strategies: (i) mass drug administration, to rapidly reduce transmission and help consolidate malaria control; (ii) intermittent preventive treatment for school-age children, to protect a high-risk yet often overlooked population; and (iii) post-hospitalization malaria prevention to decrease readmissions and mortality linked to severe malaria episodes. Conclusion Achieving malaria elimination or a substantial reduction in Angola’s disease burden demands increased political commitment, sustainable financing, professional capacity building, and rigorous monitoring. A coordinated, evidence-based approach, aligned with WHO recommendations and tailored to Angola’s epidemiological context, is essential to overcoming barriers and accelerating progress toward the 2030 malaria elimination goal.